Dahschur, Ägypten. Die Arbeiten der Frühjahrskampagne 2018 - Rosenow, Daniela (e-Forschungsberichte des DAI, 2019)
Archaeological work at Dahshur concentrated on excavating several structures linked to the Bent Pyramid of Snofru. A new excavation project was initiated in an area north of the valley temple of this pyramid, where settlement structures had been revealed through a geomagnetic survey. Here, the remains of a house, made of mud- and sandbricks and covering an area of about 35 × 30 m, came to light. All pottery fragments date to the early 4th dynasty, possibly linking the house to the process of pyramid building. Excavations were continued in three areas already under study in the past: the harbour and the lower causeway, as well as a transportation ramp made of limestone blocks originally deriving from the valley temple of the Bent Pyramid.